Criminal liability for offenses is related to corruption in sports - Yurii Kuryliuk; Hanna Shvedova; Mykola Karpenko; Yaroslav Kushnir; Nazariy Sitsinskiy (Universidad de Murcia, 2022)
Article accepted. The article will be published here soon. Pending final quality checks.